Implementasi MBKM melalui Pengembangan Kegiatan Mahasiswa dalam Mengatasi Permasalahan di Masyarakat Desa Hulawa - Djuko, Rapi Us.; Napu, Yakob; Isa, Abd. Hamid (Universitas Negeri Gorontalo, 2024)
Real Work Lecture (KKN) is a form of student service to the community and a part of the Tri Dharma of Higher Education. By holding KKN, it is hoped that a student will become more mature with his scientific discipline. KKN also seeks to create a more effective education, education that is directly experienced by students. So it is not just material but more important is the application of the theories that have been obtained in college which must be applied in the community environment because sometimes the theories that have been obtained in college are not the same as the reality in the community environment. The implementation of the KKN program is packaged under the theme